THE TRADITION OF PILGRIMAGE TO THE TOMB OF SULTAN MAULANA HASANUDDIN IN BANTEN AS A CULTURA HERITAGE AND SPIRITUALITY OF THE COMMUNITY - Titi Stiawati; Ima Maisaroh; Abdurohim Abdurohim; Nida Aeni (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The tradition of visiting the tomb of Sultan Maulana Hasanuddin of Banten is a socio-religious practice that remains alive today and plays a significant role in the lives of the people of Banten. This tradition not only reflects religious rituals but also embodies historical, cultural, and spiritual values that shape the identity of the local community. This study aims to examine the tradition of visiting the tomb of Sultan Maulana Hasanuddin of Banten as a cultural heritage and a manifestation of the community’s spirituality. The research method employed is a qualitative approach using literature review and archival research. Data were obtained from historical books, scientific journal articles, theses, research reports, and other relevant supporting sources related to the study of pilgrimage, local Islamic culture, and the Sultanate of Banten. Data analysis was conducted using a descriptive-qualitative technique by examining and interpreting various sources to uncover the meanings, practices, and dynamics of the pilgrimage tradition. The results of the study indicate that the tradition of visiting the tomb of Sultan Maulana Hasanuddin possesses a strong spiritual dimension as a means of drawing closer to Allah, a medium for self-reflection, and the formation of individual and collective spirituality. Furthermore, the pilgrimage tradition also functions as an intangible cultural heritage that plays a role in preserving history, transmitting cultural values, and strengthening the identity of the Banten community. Amid the development of religious tourism and modernization, the pilgrimage tradition faces dynamics that require sustainable management to ensure that religious and cultural values remain preserved. This study concludes that the tradition of pilgrimage to the tomb of Sultan Maulana Hasanuddin of Banten is an important and relevant cultural-religious practice in maintaining the sustainability of the community’s spirituality and cultural identity.